Implementation of Outcome Based Education (OBE) Principles in the Curriculum of the English Education Study Program at a Higher Education in Toraja - Markus Deli Girik Allo; Elim Trika Sudarsi; Nilma Taula’bi’ (Universitas Cokroaminoto Palopo, 2024)
The aim of this study is to elaborate how the implementation of the principles of Outcome-Based Education (OBE) in the curriculum of the English Education Study Program at Universitas Kristen Indonesia Toraja. The researchers applied qualitative methods with a case study design. The subjects of this study were five representative lecturers from the Research Group of the English Education Study Program, they were selected using purposive sampling techniques. Data collection in this study used observation and interview. The data analysis techniques used were transcription and coding to analyze observational data, while interviews were analyzed using thematic analysis. The results of this study confirm that the implementation of the principles of Outcome-Based Education (OBE) in the curriculum of the English Language Education Study Program UKI Toraja Indonesia is as follows: 1) The PEO preparation process not only reflects a commitment to the quality of education, but also maintains the relevance of the study program to the needs of industry and society in general, 2) PLO is described in detail and hierarchically, covering various aspects of skills and knowledge relevant to the study of English Language Education, as well as accommodating the specific needs of the intended field of study, 3) Curriculum formulation applies the principles and practices such as details on each course and learning activities, active learning approach, use of technology, integration of formative assessment, orientation to Outcome-Based Education (OBE), curriculum structure oriented to competency development, and the application of real-world relevant content. 4) The evaluation system implemented not only aims to assess student achievement, but also to ensure that their curriculum is relevant, effective, and prepares graduates to succeed in their careers and make a positive contribution to the development of society.